2020
DOI: 10.2319/051619-335.1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term stability of miniscrew anchored maxillary molar distalization in Class II treatment

Abstract: Objective To investigate treatment stability of miniscrew-anchored maxillary distalization in Class II malocclusion. Materials and Methods This retrospective study included a distalization (n = 19) and a control (n = 19) group; a patient group with minor corrections served the control. Lateral cephalograms of 38 adult patients were taken before (T0), immediately after (T1), and 3–4 years after (T2) treatment. Horizontal and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…A Class I occlusal relationship defines the gold standard when assessing the outcome of an orthodontic treatment, as described by various scores [ 27 – 29 ]. Therefore, we did not use radiographic landmarks to evaluate molar distalization, as has frequently been proposed by various authors [ 24 , 30 – 43 ]. The measurement method, which was introduced previously, is relatively simple and can be applied to each lateral segment, separately, which is of major importance particularly in asymmetric Class II cases [ 7 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…A Class I occlusal relationship defines the gold standard when assessing the outcome of an orthodontic treatment, as described by various scores [ 27 – 29 ]. Therefore, we did not use radiographic landmarks to evaluate molar distalization, as has frequently been proposed by various authors [ 24 , 30 – 43 ]. The measurement method, which was introduced previously, is relatively simple and can be applied to each lateral segment, separately, which is of major importance particularly in asymmetric Class II cases [ 7 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, several devices such as headgear and pendulum appliances have been used to distalize maxillary molars during nonextraction treatment, [1][2][3] but some studies achieved successful distalization using buccal miniscrews. [4][5][6][7] In addition, anchor plates in the zygomatic buttress and modified C-palatal plates (MCPPs) have been reported to distalize maxillary molars. [8][9][10][11][12][13][14][15][16] When using nonextraction treatment to achieve posterior movement of molars in adolescents, the third molars' initial position needs to be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, several devices such as headgear and pendulum appliances have been used to distalize maxillary molars during nonextraction treatment, 1‐3 but some studies achieved successful distalization using buccal miniscrews 4‐7 . In addition, anchor plates in the zygomatic buttress and modified C‐palatal plates (MCPPs) have been reported to distalize maxillary molars 8‐16 …”
Section: Introductionmentioning
confidence: 99%
“…According to recent studies, the centres of resistance of the maxillary arch have been found around the mid-root of the second premolar (11.0 mm apical and 26.5 mm posterior to the incisal edge of the maxillary central incisor) 10 and that of the mandibular arch, between the second premolar and the first molar (13.5 mm apical and 25.0 mm posterior to the incisal edge of the mandibular central incisors). 11 Therefore, force vectors passing through these areas may lead to arbitrary displacement of the whole arch, according to the relationship between the specific centre of resistance and the force lines. If the line of force connecting the head of the miniscrew and the hook passes horizontally through the centre of resistance, the whole arch is moved posteriorly, viz.…”
Section: A-p and Verti C Al Total Arch Movementmentioning
confidence: 99%
“…Hence, when treating end‐to‐end Class II patients, the dual miniscrew can achieve clinically significant treatment results. Bechtold et al 11 also reported that for Class II malocclusion, total arch distalization using inter‐radicular miniscrews placed between the maxillary second premolar and the first molar can move the maxillary first molar posteriorly by an average of 4.2 mm without distal inclination. A mesial movement of the first molar by an average of 0.7 mm was reported during the post‐debonding observation period of about 42 months, indicating that the result of this therapy is clinically stable.…”
Section: A‐p and Vertical Total Arch Movementmentioning
confidence: 99%